Penerapan Model Pembelajaran Learning Together (LT) Pada Teks Biografi Dengan Menggunakan Media Canva Untuk Meningkatkan Motivasi Belajar Kelas X TITL SMKN 1 Bagor - Pungki Hanafi; Sri Lestari; Elly Triwidodo (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research is a classroom action research (PTK) which aims to increase the learning motivation of class X TITL students of SMK Negeri 1 Bagor, through Learning Together (LT) learning in Indonesian language lessons by building students' creativity in writing biographical texts. The background of this research was taken because it saw that there were still many weak students' motivation in learning activities in class. This research method uses a descriptive model that emphasizes a qualitative approach that is compiled through the stages of observation, planning, implementation, reflection, and revision. Data collection techniques in this study were through tests, observations, and questionnaires. Based on the data analysis carried out that the use of the biographical text learning model in Indonesian subjects using the Learning Together (LT) learning method at SMK Negeri 1 Bagor, there are 2 implementation cycles and each cycle is carried out 1 biographical text writing test, which will be carried out 2 times the test or 2 times the cycle. In the results of data analysis in cycle 1, there is an average student score of 70.33, which can be interpreted as incomplete because the standard KKM score is 75. Meanwhile, in the second cycle, the student learning outcomes have increased, namely with an average value of 80. with the completeness score of 25 students out of 36. The conclusion that can be drawn based on the results of the study is that the use of the Learning Together (LT) learning method in biographical texts can have a positive impact on increasing student learning motivation and student learning outcomes. Keywords: Writing Skills; Learning Motivation; Biographical Texts; Infographics; Together Learning; Classroom Action Research.